«Два романа одного жизнеописания»: «Три года» А.П. Чехова и «Братья Карамазовы» Ф.М. Достоевского - КОМЯТИ, ДИАНА (SlavVaria, 2021)
“Two novels of one biography”: “Three years” by A.P. Chekhov and “The Brothers Karamazov” by F.M. Dostoevsky. In contemporary Chekhov studies the significance of Dostoevsky’s creative heritage in Chekhov’ artistic world is increasingly comprehended. They attempt to reveal and interpret intertextual connections with Dostoevsky’s novels, embedded in the subtext of Chekhov’s works. On the one hand, common themes and problems that bring writers closer together are revealed, on the other hand, Chekhov’s polemical rethinking of Dostoevsky’s legacy is noted. Connected with this tendency the article deals with comparative analysis of Chekhov’s story “Three Years” and Dostoevsky’s novel “The Brothers Karamazov”. In this work we try to identify and interpretate the allusions and parallels hidden in Chekhov’s story.